Optimizing graphene anode performance in lithium-ion batteries: investigating the effects of diverse thermal conditions - Ng, Zen Ian (John Wiley and Sons Inc, 2024)
Herein, the graphene nanoplatelets (GNPs) anode is prepared using a facile, chemical-free, and scalable approach that combines probe sonication and microwave treatment in an argon condition. The resulting GNPs exhibit a significant number of structural defects (ID/IG: 0.262), which provide abundant active sites to store lithium ions and offer sufficient pathways for the quick transfer of lithium ions and electrons. In lithium-ion batteries (LIBs), the GNPs anode exhibits an outstanding electrochemical performance, achieving a high reversible 414 mAh g−1 capacity at the high current density of 1 A g−1 after 350 cycles. The anode maintains desirable capacities of 167 and 150 mAh g−1 even at elevated current densities of 4 and 5 A g−1, respectively. Importantly, it exhibits remarkable cycling performance with more than 100% of the initial reversible capacity retention after 350 cycles. The outcomes show noticeably enhanced performance characteristics, suggesting the potential for developing microwave-treated graphene anode for long-lasting and high-performance LIBs.